Profile of hepatitis carriers in the State of Rio de Janeiro, from 2010 to 2018 (Research, Society and Development, 2021)
Objective: To characterize the profile of individuals with hepatitis A in the State of Rio de Janeiro, from 2010 to 2018. Methodology: This is a cross-sectional research developed in the quantitative approach. Secondary data from the Viral Hepatitis Notification Form of the Bank of the Notifiable Diseases Information System, provided by the State Health Secretariat of Rio de Janeiro, were used. Results: 48672 notifications were analyzed, of which 3734 were confirmed notifications of hepatitis A carriers only, 28719 were related to other hepatitis, 614 were co-infected with more than one viral hepatitis and 15605 were ignored. The highest prevalence of hepatitis A was found in individuals with 4 to 8 years of study, black, aged ≤ 24 years and with contaminated water and food being the main source of contagion. Conclusion: Notification of cases and proper completion is important for the definition of health actions capable of mitigating damage to public health.